Klocki LEGO - zabawka dla dzieci i afoli. Konteksty edukacyjne oraz pedagogiczne - Nowak-Kluczyński , Konrad (Studia Edukacyjne, 2023)
LEGO bricks are undoubtedly one of the most famous and strong construction toy brands. The name comes from the Danish phrase “leg godt” which means “play well”. The company motto is: “Only the best is good enough”. The bricks have limitless capacities. They are used not only for playing but more and more often in the educational context, from kindergarten to universities. LEGO is creativity and play as well as stimulation of mental development. The bricks excite the imagination of both children and adults. In the therapy, they improve focus, concentration, logical thinking and improve small motor skills. Nowadays, they are encroaching the adult world boldly, because they have become strong icon of pop culture and the socially engaged “toy”. LEGO sets produced especially for AFOLs (the acronym of “an adult fan of LEGO”) strengthen hobby development. They are collector’s items as well as a sentimental journey to the childhood and, especially, a supporting gesture for marginalizing environments.